Once an Impression Manager, Always an Impression Manager? Antecedents of Honest and Deceptive Impression Management Use and Variability across Multiple Job Interviews - Roulin, Nicolas; Bourdage, Joshua S. (Frontiers in Psychology, 2017)
Research has examined the antecedents of applicants’ use of impression management (IM) tactics in employment interviews. All existing empirical studies have measured IM in one particular interview. Yet, applicants generally interview multiple times for different positions, and thus have multiple opportunities to engage in IM, before they can secure a job. Similarly, recent theoretical advances in personnel selection and IM research have suggested that applicant behaviors should be considered as dynamic and adaptive in nature. In line with this perspective, the present study is the first to examine the role of individual differences in both applicants’ use of IM tactics and the variability in IM use across multiple interviews. It also highlights which honest and deceptive IM tactics remain stable vs. vary in consecutive interviews with different interviewers and organizations. Results suggest that applicants high in Extraversion or core self-evaluations tend to engage in more honest self-promotion but do not adapt their IM approach across interviews. In contrast, applicants who possess more undesirable personality traits (i.e., low on Honesty-Humility and Conscientiousness, but high on Machiavellianism, Narcissism, Psychopathy, or Competitive Worldviews) tend to use more deceptive IM (and especially image creation tactics) and are also more likely to adapt their IM strategy across interviews. Because deceptive IM users can obtain better evaluations from interviewers and the personality profile of those users is often associated with undesirable workplace outcomes, this study provides additional evidence for the claim that deceptive IM (or faking) is a potential threat for organizations.